PENGARUH PENGGUNAAN FITUR PRESENTASI APLIKASI CANVA TERHADAP MINAT BELAJAR SEJARAH PESERTA DIDIK KELAS XI IIS SMA KEMALA BHAYANGKARI 1 KUBU RAYA - Riah, Kama; Ulfah, Maria; Mirzachaerulsyah, Edwin (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to see the effect of using the presentation feature of the Canva application on the interest in learning history of class XI IIS students at SMA Kemala Bhayangkari 1 Kubu Raya. This research is quantitative in the form of Quasi Experimental Design. The population in this study was 133 students, while the sample was 56 students. Divided into two class samples, namely 28 experimental class samples and 28 control class samples. In taking samples, researchers used Probality Sampling with the Cluser Sampling type. Data was collected using questionnaires, observation and documentation. The results of hypothesis testing using a linear regression test which shows that there is a linear relationship between the independent variable and the dependent variable in the experimental class has a unidirectional relationship, namely Y= 14.933 + 0.788 X with a large significance of 0.00 < 0.05. This result is also strengthened by an independent t-test with a significance of 0.00 < 0.05. The average percentage result for the experimental class was 85.15% which was in the very high category. The response given by students was very good with an average percentage of 84.6%. The conclusion of this research is that there is an influence of using the presentation feature of the Canva application on the learning interest of class XI IIS students at SMA Kemala Bhayangkari 1 Kubu Raya.